Penggunaan Media Sosial terhadap Penyalahgunaan Obat Terlarang pada Remaja - Mia Audina (Jurnal Ilmiah Kesehatan Sandi Husada, 2019)
Abstract. There are many factors that can influence teens to abuse drugs and using illegal drugs. In this social media era, it is well known that the Internet has the greatest influence on its users, positively and negatively, and one of them is promoting drug abuse and the use of illegal drugs. The internet is a gateway to information. Open access to information makes it difficult to filter information received both positive and negative. In addition, the internet is also a tool for communication. Thus making communication much easier than before. Open access to information and communication channels can be used negatively by adolescents, especially in relation to drug abuse, research presented in this article has proven that social media such as Twitter, Facebook and others become a place for buying and selling and disseminating information about drugs and abuse drugs